Feeding Habits in the Cultural Domains of Child Care: Elements for Health Promotion - Martínez-López, Yolanda; Salvador-Moysén, Jaime; Alfaro-Alfaro, Noé (Frontiers in Public Health, 2021)
Introduction: Family eating behavior is determined by the meaning that the caretaker gives to food and the act of eating in the domestic environment, as well as the beliefs and perceptions around those concepts. Objective: Identify the place that nutrition has within the dimensions of child care, the specific weight that the caregiver gives to it within the range of actions deployed and if there are differences when the child exhibits neurodevelopmental disorders, as a contribution to the design of interventions in health promotion. Methodology: Qualitative, exploratory, two-stage study, with the approach of cognitive anthropology; proposal sampling of maximum differences, 121 informants participated in three groups, caregivers of: (1) healthy children, (2) children who had been hospitalized between 3 and 6 months prior to the time of the interview, and (3) children with a diagnosis of permanent neurological injury and that express some type of neurodevelopmental disorder. Results: Nourishment is the element that reaches the highest values of cultural relevance in the three groups, is located in different domains according to the condition of the care receiver. Conclusion: The common domains are Well-being, Health Maintenance, Coexistence, and Security, in the 3rd group the domain of Socialization emerges, the elements that make up the conceptual dimensions were identified, the comparative design allowed to identify differences. The description of the domains can represent the cognitive spaces of educational intervention and the elements that configure them are the triggers of the interaction, due to the importance they are given in everyday life.